Analysis Of The Influence Of Leadership, Work Discipline And Compensation On Performance Of State-Owned Pawnbroker Employees In Indonesia - Ratih Pratiwi; Arifhan Ady Dj; Nurlelasari Ginting; Arifuddin; H.M.Anwar (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The competition amongst Indonesian pawn services, both state-run and commercial, has intensified in the contemporary globalization age. In this study, Pegadaian is one of the government-owned pawn service branches, was examined by researchers. The purpose of this study is to ascertain if or to what extent the factors of work discipline, leadership, and salary affect employee performance. This study makes use of quantitative methodologies and data gathering strategies that include questionnaire distribution and library data. Thirty employees made up the study's sample. Multiple linear regression is the data analysis method that is employed with SPSS. Additionally, the impact of leadership, work discipline, and salary on employee performance is seen in hypothesis testing. The corrected R Square value, derived from multiple linear regression analysis, is 60%. Thus, it makes sense that factors related to work discipline, leadership, and remuneration account for 60% of the variance in employee performance.